The impact of pandemic COVID-19 on remittances and macroeconomy fundamental in ASEAN 6 - Siti Komariyah; Lilis Yuliati; Moh Adenan; Fajar Wahyu P (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
Globalization and liberalization increasingly provide opportunities for each country to increase regional and global cooperation. Socio-economic integration is also increasing, along with community cooperation in the regional and global scope. This study aims to determine the effect of remittances and other macroeconomic variables such as FDI, inflation, and export-import on GDP per capita in ASEAN 6 countries. The panel data analysis method used is regression using panel data sourced from the World Bank and ASEAN datasets in the form of annual data. The estimation results from FEM found that exports and remittances showed a significant positive effect on GDP per capita in ASEAN 6. In addition, imports showed a significant negative effect on GDP per capita in ASEAN 6. Meanwhile, several macroeconomic variables that were not significant were FDI, which showed a significant negative effect. Positive but not significant, inflation has a negative but not significant effect on GDP per capita in ASEAN 6. The emphasis on the positive effect of remittances on GDP per capita proves that the flow of remittances into developing countries will help increase income per capita. Vice versa, a crisis that hinders the increase in the enthusiasm of emigrants. The COVID-19 pandemic delays the emigrant's production activities and increases that will hinder the flow of remittances into the country of origin, such as in ASEAN 6 countries.